Emerging Jurisprudence on Intellectual Property Rights Pertaining to Generative AI: Comparative Law and Contemporary Judicial Interpretations - M.P.Ramaswamy (International Journal of Scientific Research and Innovative Studies, 2024)
The advent of generative artificial intelligence (AI) and its increasing applications in various walks of life, albeit generally perceived as utilitarian, raises a wide range of questions regarding its potential implications. Among them, legal and regulatory challenges facing generative AI gain significance due to the indispensable need for legal certainty, which is essential for developing and deploying generative AI in various professional and personal pursuits. Although significant economies worldwide have formulated aspiring policies for leadership in AI development, specific initiatives to create a congenial legal environment are sparse. Despite some regional initiatives and national regulatory standards are starting to emerge, lack of harmonization and a concerted approach are conspicuous. While more international initiatives to establish legal standards governing AI are expected, many national jurisdictions still rely on their existing general legal regimes to govern AI-related developments. However, with the faster growth of generative AI and its wider adoption and accessibility across borders, national courts are increasingly confronted with unprecedented legal claims and regulatory issues. The paper assesses some legal standards and early judicial responses related to generative AI. It identifies evidence of some diversity in national responses and its implications for the development and use of generative AI in key economies. The paper specifically focuses on the intellectual property rights (IPR) issues related to copyrights in works produced by generative AI. It compares the two significant jurisdictions of USA and China as representations of civil and common law legal systems, respectively. The paper reviews the copyright regimes and legal standards pertinent to the use of generative AI in the two jurisdictions. It closely examines the emerging judicial jurisprudence in the two jurisdictions tackling copyright claims related to generative AI and identifies its potential implications. The paper concludes by assessing the need for relevant international treaty regimes to seek a more harmonized legal framework to promote sustainable development and broader use of generative AI. Keywords: Generative Artificial Intelligence, Intellectual Property Rights, Judicial Interpretations, Comparative Law Received Date: April 17, 2024 Accepted Date: May 14, 2024 Published Date: June 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/159 DOI:https://doi.org/10.5281/zenodo.11267516